The Influence of Capital Structure on Profitability: Panel Regression Analysis of Indonesian State-Owned Enterprises in the Energy and Mining Sector from 2019 to 2023 - Najmah Rizqya Maliha Putri; Adeliya Fernanda (International Journal of Quantitative Research and Modeling, 2025)
Capital structure is an important factor in financial decision-making that can influence a company's profitability level. Indonesian state-owned enterprises (BUMN) in the energy and mining sector have high capital needs and significant exposure to external risks, making capital structure efficiency crucial. This study aims to analyze the impact of Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) as a profitability indicator for Indonesian state-owned enterprises in the energy and mining sector in Indonesia during the period 2019–2023. This research uses six companies as samples, namely PT Aneka Tambang Tbk., PT Bukit Asam Tbk., PT Indonesia Asahan Aluminium, PT Pertamina (Persero), and PT Timah Tbk. The study employs a quantitative approach with a panel data regression method. Data was obtained from the annual financial statements of the company. The analysis process was conducted thoroughly using Eviews 12 software, including data processing, assumption testing, selection of the panel regression model, and final estimation. The results of the analysis indicate that the Random Effect Model is the most suitable approach. Simultaneously, DER and DAR have a significant effect on ROE. However, partially, only DER has a significant negative effect, while DAR is not significant. These findings indicate that the capital structure, specifically the proportion of debt to equity, plays an important role in determining the company's profitability. Therefore, optimal management of the financing structure becomes an important strategy for the company in maintaining long-term financial performance.